Marine Tardigrada from the Mexican Caribbean with the description of Styraconyx robertoi sp. nov. (Arthrotardigrada: Styraconyxidae) - Pérez-Pech, Wilbert Andrés; de Jesús-Navarrate, Alberto; Demilio, Erica; Anguas-Escalante, Abril; Hansen, Jesper Guldberg (Zootaxa, 2020)
Marine tardigrades were sampled at three sites on Mexico’s Caribbean coast. Eleven taxa were collected, one of which is described as a new species. Styraconyx robertoi sp. nov. is characterized by: asymmetric primary clavae; dorsal cuticle with a grid-like sculpture; claws with reduced accessory hooks; females with peduncles on only two digits (the external) of legs I–IV; males with peduncles only on the external digits of legs I–III and peduncles on all four digits of leg IV. Styraconyx robertoi sp. nov. is most similar to S. craticuliformis Chang & Rho, 1998 and S. kristenseni Renaud-Mornant, 1981 by having asymmetric primary clavae but differs from S. craticuliformis mainly by the number of peduncles and from S. kristenseni mainly by the presence of a grid-like dorsal sculpture. Additionally, a comparison of material collected from the same region, but reported previously only as genus level records, was carried out in order to produce a refined list of the known Mexican marine tardigrade species.